A cognitive stylistic analysis of K.S. Maniam's in a far country - Chong S.T.; Rahman A.Z.A.; Kaman Z.K.; Leon C. (American Institute of Physics Inc., 2024)
Although stylistic analysis is the most popular approach in the learning and teaching of an introductory analysis to novels, a very little pedagogical demonstration has been done in the field. One reason is that reader response and postcolonialism approaches are more familiar to the students. Hence, this paper discusses the learning and teaching of K.S. Maniam's In a Far Country to Malaysian students using linguistic analysis. Specifically, this paper demonstrates the use of stylistics in exploring the text in relation to the major themes and tropes as well as text and context. The reason for studying K.S. Maniam is because he is one of the most prominent writers in the domain of Malaysian literature in English. He has written three novels, two plays, numerous short stories, and a sea of poetry. This study focuses on In a Far Country. It is a set text that has been used in Malaysian schools and universities. It is often used as a set text because it delves into nationalism, identity, culture, diaspora, and other pertinent issues that are very much important for the students to grapple. Hence, this paper demonstrates the stylistic analysis of the text. Students have shown some aspects of the analysis and how this analysis entails meaning-making. 2023 Author(s).